Report of a Network Coordinating Group on Forages: Ad hoc meeting, 11 May 2009, La Rochelle, France - Veteläinen, M.; Willner, E.; Marum, P.; Boller, B.; Bioversity International (2009)
Report of a Network Coordinating Group on Forages, ad hoc meeting, 11 May 2009, La Rochelle, France